The Gateway Structure: Hierarchical Integration and Indigenous Agency in Satyahangma's Bhakti Songs - Lungeli, Dipak (NPRC Journal of Multidisciplinary Research, 2026)
This paper examines selected Bhakti songs of Satyahangma (true religion), a Limbu religious cult from the collection of Bairagi Kainla’s The Preaching of Phalgunanda and the Hymns of Satyahangma (1990). The corpus informs Phalgunanda Lingden's early twentieth-century reformation movement operating within Limbu indigenous communities of eastern Nepal as an illustration of reformative syncretism. Drawing theory from the corpus itself, the article argues that Phalgunanda's syncretism constitutes the structured act of religious border navigation strategy. The gateway structure selectively incorporates elements from Hindu Josmani devotional practice and Buddhist ritual technology. Yet, it prioritizes the Mundhum consciousness, the foundational epistemological matrix of Limbu identity as the interpretive authority governing all external borrowings. Therefore, the syncretism does not imply the religious capitulation to dominant religious forces but informs the resistance against their overriding influence upon the indigenous practice. The corpus theorizes religious syncretism as a principle through which Limbu communities traverse religious borders without surrendering their Mundhum core. The inductive analysis of Satyahangma Bhakti songs reveals them as theoretically generative instance of indigenous agency. They complicate the essentialist notion of syncretism as assimilation and the postcolonial reading of religious hybridity as subversion.